(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Vulvar cancer is a rare gynecological malignancy that predominantly affects elderly women and is often associated with poor outcomes in advanced stages. Recurrent and metastatic vulvar cancer represents a significant clinical challenge due to limited treatment options and resistance to conventional therapies such as surgery, radiotherapy, and chemotherapy. In recent years, immunotherapy has emerged as a promising therapeutic approach in the management of advanced gynecological cancers, including vulvar cancer. This article aims to review the role of immunotherapy in the treatment of recurrent and metastatic vulvar cancer, with a particular focus on immune checkpoint inhibitors and tumor immune microenvironment interactions. Current clinical evidence suggests that immunotherapeutic strategies may offer meaningful clinical benefits in selected patients, especially those with programmed death-ligand 1 (PD-L1) expression, high tumor mutational burden, or human papillomavirus (HPV)-associated disease. Understanding the immunological mechanisms and identifying predictive biomarkers are essential for optimizing treatment outcomes and improving survival in patients with advanced vulvar cancer.